Skin toxicity after chest wall/breast plus level III-IV lymph nodes treatment with helical tomotherapy. (26th November 2018) - Lancellotta, Valentina; Chierchini, Sara; Perrucci, Elisabetta; Saldi, Simonetta; Falcinelli, Lorenzo; Iacco, Martina; Zucchetti, Claudio; Palumbo, Isabella; Bini, Vittorio; Aristei, Cynthia
Abstract: Introduction: To evaluate the incidence of toxicity in breast cancer with helical tomotherapy (HT). Materials and Methods: 51 patients with breast cancer were assigned to postoperative radiotherapy by means of HT to the chest wall/breast plus draining nodes. During HT treatment, toxicity was monitored and were assessed using the Common Terminology Criteria for Adverse Events 4.0 scale. Results: Acute skin G3 toxicity observed in 1.9% cases. No acute or late G4 toxicity was observed. At a median follow-up of 21 months 2 patients have late G1 toxicity. Conclusions: HT was associated with a low incidence of low-grade skin toxicity.